The Global Macroeconomic Costs of Raising Bank Capital Adequacy Requirements - Vitek, Francis (IMF Working Papers; Working Paper ;, 2012)
This paper examines the transitional macroeconomic costs of a synchronized global increase in bank capital adequacy requirements under Basel III, as well as a capital increase covering globally systemically important banks. The analysis, using an estimated multi-country model, contributed to the work of the Macroeconomic Assessment Group analysis, especially in estimating the potential international spillovers associated with a global increase in capital requirements. The magnitude of the effects found in this analysis is relatively modest, especially if monetary policies have scope to ease in response to a widening of interest rate spreads by banks.